Excitatory subtypes of the lateral amygdala neurons are differentially involved in regulation of synaptic plasticity and excitation/inhibition balance in aversive learning in mice - Morishima, Mieko; Matsumura, Sohta; Tohyama, Suguru; Nagashima, Takashi; Konno, Ayumu; Hirai, Hirokazu; Watabe, Ayako M. (Frontiers in Cellular Neuroscience, 2023)
The amygdala plays a crucial role in aversive learning. In Pavlovian fear conditioning, sensory information about an emotionally neutral conditioned stimulus (CS) and an innately aversive unconditioned stimulus is associated with the lateral amygdala (LA), and the CS acquires the ability to elicit conditioned responses. Aversive learning induces synaptic plasticity in LA excitatory neurons from CS pathways, such as the medial geniculate nucleus (MGN) of the thalamus. Although LA excitatory cells have traditionally been classified based on their firing patterns, the relationship between the subtypes and functional properties remains largely unknown. In this study, we classified excitatory cells into two subtypes based on whether the after-depolarized potential (ADP) amplitude is expressed in non-ADP cells and ADP cells.Their electrophysiological properties were significantly different. We examined subtypespecific synaptic plasticity in the MGN-LA pathway following aversive learning using optogenetics and found significant experience-dependent plasticity in feed-forward inhibitory responses in fear-conditioned mice compared with control mice. Following aversive learning, the inhibition/excitation (I/E) balance in ADP cells drastically changed, whereas that in non-ADP cells tended to change in the reverse direction. These results suggest that the two LA subtypes are differentially regulated in relation to synaptic plasticity and I/E balance during aversive learning. that associative plasticity in the LA may be the underlying mechanism of the CS-US association in Pavlovian aversive learning (Rogan et al., 1997).Excitatory cells are the major group of neurons in the LA. It is well known that excitatory cells are heterogeneous in their firing patterns, projection patterns, morphologies, and transcriptomes